Desktop analysis of potential impacts of visitor use: A case study for the highest park in the Southern Hemisphere - Barros, A.; Pickering, C.; Gudes, Ori (Academic Press, 2015)
Nature–based tourism and recreation activities have a range of environmental impacts, but most protected area agencies have limited capacity to assess them. To prioritise where and what impacts to monitor and manage, we conducted a desktop assessment using Geographical Information Systems (GIS) by combining recreation ecology research with data on visitor usage and key environmental features for a popular protected area used for mountaineering and trekking, Aconcagua Provincial Park (2400–6962 m a.s.l.) in the Andes of Argentina. First, we integrated visitor data from permits with environmental data using GIS. We then identified key impact indicators for different activities based on the recreation ecology literature. Finally, we integrated this data to identify likely ecological impacts based on the types of activities, amount of use and altitudinal zones. Visitors only used 2% of the Park, but use was concentrated in areas of high conservation value including in alpine meadows and glacier lakes. Impacts on water resources were likely to be concentrated in campsites from the intermediate to the nival/glacial zones of the Park while impacts on terrestrial biodiversity were likely to be more severe in the low and intermediate alpine zones (2400–3800 m a.s.l.). These results highlight how visitor data can be used to identify priority areas for on-ground assessment of impacts in key locations. Improvements to the management of visitors in this Park involves more effective ways of dealing with water extraction and human waste in high altitude campsites and the impacts of hikers and pack animals in the low and intermediate alpine zones.